Physiological Responses and Fruit Retention of Carambola Fruit (Averrhoa carambola L.) Induced by 2,4-D and GA3 - BEKTI KURNIAWATI; HAMIM HAMIM (Bogor Agricultural University, Indonesia, 2009)
One of the problems in cultivation of carambola fruit is the high of flower and fruit drop during fruit development. To understand these problems and to improve fruit retention, the content of indole-3-acetic acid (IAA) and total sugar in carambola fruit and leaves were analysed in response to application of gibberellic acid (GA3) and 2,4-dichlorophenoxyacetic acid (2,4-D). The experiments used 1,5 year old of carambola plants (Averrhoa carambola L. var Dewi) grown in polybag of 40 x 50 cm. GA3 with the concentration of 0, 20, 40, and 60 ppm and 2,4-D of 0, 5, 10, and 15 ppm were applied to the flower and the supporting leaves of carambola plant. The parameters analysed were number of flower drop, fruit formation, fruit retention, number of harvestable fruit per cluster, fruit weight per cluster, the content of sugar in the leaves and IAA in the fruit. The result showed that IAA content of the fruit increased in response to single as well as combination of GA3 and 2,4-D application. Sugar content of the leaves also increased in response to GA3 and 2,4-D application; however, the pattern was different with that of IAA. The best treatment to improve fruit retention was a single application of 10 ppm 2,4-D or 60 ppm GA3, and combined application of 5 ppm 2,4-D and 60 ppm GA3. Key words: fruit drop, fruit retention, carambola fruit, auxin, gibberellin